Do rheumatoid arthritis patients in clinical practice benefit from switching from infliximab to a second tumor necrosis factor alpha inhibitor?. Issue 9 (27th March 2007) - Hjardem, Elisabeth; Østergaard, Mikkel; Pødenphant, Jan; Tarp, Ulrik; Andersen, Lis Smedegaard; Bing, Jette; Peen, Elisabeth; Lindegaard, Hanne Merete; Ringsdal, Vibeke Stevenius; Rødgaard, Anne; Skøt, Jens; Hansen, Annette; et al.
Abstract : Objective: To investigate the efficacy of switching to a second biological drug in rheumatoid arthritis (RA) patients. Methods: Since 2000, Danish RA patients (n = 1021) receiving biological therapy have been registered in the nationwide DANBIO database. The first and second treatment series of patients, who switched therapy before 2005 (n = 235), were analysed for their reasons for switching, Disease Activity Score 28 (DAS28), DAS28 improvement, European League against Rheumatology (EULAR) response and drug survival. Most patients switched from infliximab to etanercept or adalimumab. Results: Median survivals for switchers' first/second treatment were 37/92 weeks (all patients' first treatment 119 weeks). Reasons for switching were lack of efficacy (LOE; 109 patients), adverse events (AE; 72), other reasons (54). If patients experienced AE to the first drug, 15% had AE to the second. Median DAS28 improvements in first/second treatment at 3 months were: LOE switchers 1.1/1.6; AE switchers 1.5/0.8. In LOE switchers, a good/moderate EULAR response was more prevalent during the second treatment course than during the first (63% versus 54%, p = 0.02). AE switchers achieved similar EULAR responses to both treatments (59% versus 50%, p = 0.38). Conclusion: LOE switchers had a better clinical response to the second treatment. AE switchers responded equally well to both treatments, with a low risk of discontinuing the second drug as a result of AE. Drug survival of the switchers' second biological therapy was higher than of the first, but lower than that of non-switchers. No difference between various sequences of drugs were found. Danish post-marketing data thus support that RA patients may benefit from switching biological therapy.